"Matka Jego zachowywała wszystkie te słowa w sercu" (Łk 2, 51b) - Tronina, Antoni (The Biblical Annals, 2017)
1. The sanctuary in Jerusalem has always been a place in which the word of God is present amidst Israel. St. Luke adds the Christological aspect to the biblical theology of the temple. 2. The third Gospel from its beginning points to Jesus as the genuine and ultimate Temple of the new People of God, the place of a salvific encounter between God and man. The Acts of the Apostles transpose these symbols on the Church. 3. The Gospel of Childhood according to St. Luke emphasises the role of Mary in the history of salvation. The Mother of Jesus is the icon of the Church and model for all disciples, whose “heart” should a living temple of the Word. 4. The biblical Revelation ends with a vision of “the holy city Jerusalem coming down out of heaven from God” (Acts 21:10). There is no temple in this city, for its Temple is the Lord, God almighty, and the Lamb (Acts 21:22).